2020
DOI: 10.1097/aog.0000000000004005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Coronavirus Disease 2019 (COVID-19) Illness in Symptomatic Pregnant and Postpartum Women Stratified by Hispanic Ethnicity

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 3 publications
7
43
0
Order By: Relevance
“…Compared to the general Labor and Delivery population at MGH, women enrolled in the biorepository were more likely to be Hispanic, publicly-insured, and Spanish-speaking. These demographics are consistent with our prior work demonstrating that pregnant women of Hispanic ethnicity who receive prenatal care at MGH community health centers have been disproportionately impacted by COVID-19 [22].…”
Section: Generalizability and Representativeness Of The Cohortsupporting
confidence: 89%
See 2 more Smart Citations
“…Compared to the general Labor and Delivery population at MGH, women enrolled in the biorepository were more likely to be Hispanic, publicly-insured, and Spanish-speaking. These demographics are consistent with our prior work demonstrating that pregnant women of Hispanic ethnicity who receive prenatal care at MGH community health centers have been disproportionately impacted by COVID-19 [22].…”
Section: Generalizability and Representativeness Of The Cohortsupporting
confidence: 89%
“…Attempts to develop biobanks from other devastating pandemics, such as the Ebola crisis in West Africa [ 31 ], have also shown that identifying infrastructure gaps and points of cultural sensitivity are critical to achieving a successful biobank relevant to the population it serves. Data from our group and others have demonstrated that COVID-19 disease has disproportionately affected people of color and lower socioeconomic status [ 22 , 32 – 35 ], widening health disparities. The recruitment of study staff members fluent in Spanish to facilitate the full understanding and inclusion of women from the hardest-hit communities in Massachusetts, and making changes to our enrollment and sample collection processes that sensitively responded to the stressors experienced by our pregnant and delivering women, were critical to the success and inclusivity of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study findings nonetheless offer important insights into the impact of the pandemic on pregnant women and offer a compelling basis for further systematic research in this area. Studies assessing the experiences of women of color are especially critical because stress-related burdens and health inequities affecting women of color have increased during the COVID-19 pandemic and may be exacerbating existing disparities in reproductive health outcomes pandemic ( Goldfarb et al, 2020 ; Onwuzurike et al, 2020 ). Additional studies identifying resilience factors such as social support and access to mental health resources, as well as epidemiological and clinical studies are urgently needed.…”
Section: Limitationsmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), caused by the virus known as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), affects racial and ethnic minorities and socioeconomically disadvantaged groups disproportionately. 1 , 2 , 3 It remains uncertain how the proportions of positive SARS-CoV-2 test results have changed over time among pregnant women from socially vulnerable populations after the closure of nonessential businesses and schools, and promotion of social distancing measures. We evaluated the temporal trends, regional geographic variation, and racial and ethnic disparity in SARS-CoV-2 prevalence among pregnant women presenting to obstetrical units of a large health system in New York during the COVID-19 outbreak.…”
Section: Objectivementioning
confidence: 99%